Eficiência na aplicação do perifíton heterotrófico em diferentes substratos artificiais e naturais no desempenho zootécnico de Tilápias do Nilo - Freitas, Robério Mires de (2021)
Tilapia have characteristics and attributes that make them an ideal species for cultivationin intensive systems. This cultivationpattern usually raises questions about environmental sustainability. Alternatives have been sought to mitigate environmental problems such as the manipulation of natural communities in aquatic systems such as periphytic biofilm. Basically, microbial communities can benefit from high nutrient loads by promoting improved water quality and improving cultivationperformance. The present study aimed to evaluate the colonization process and stability of the periphytic biofilm in indoor conditions and in different types of submerged substrates, analyzing their influence on the maintenance of water quality, zootechnical performance and resistance of juveniles of Oreochromis niloticusagainst the pathogen Pseudomonas aeruginosa. The research was carried out Instituto de Ciências do Mar –Labomar, where was evaluated the performance of the periphytic biofilm formed by a bacterial consortium consisting of Rhizobium rosettiformans; Pseudomonassp; Enterobactersp; Burkholderia spin the culture of Nile tilapia. For this, the development of biofilm occurred in different materials as substrates, being used in different treatments (T1 flexible plastic nets; T2 PVC plates; T3 natural jute fiber and T4 control absence of substrates). The colonization of the microbial community was modified by the type of material used as a substrate, with differences in the bacterial quantification and components of the zooperifiton. The presence of biofilm in the cultivationenvironments provided better growth for fish and resistance to Pseudomonas aeruginosa when compared to the control treatment, but the results did not differ between treatments with different substrates. No influence of biofilm on water quality parameters was seen.